Upaya Preventif Demoralisasi Siswa melalui Pendidikan Karakter Berbasis Pedagogik Profetik - Resi Endang; Yusuf Tri Herlambang; Tatang Muhtar (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Prophetic-based character education should be implemented to students. This is because by applying this, the demoralization of students' character can be prevented as seen from previous research results and discussions covering topics such as prophetic pedagogy addressing character decadence, prophetic pedagogical values in Islamic religious education, and strengthening the orientation of Islamic religious identity in prophetic pedagogy. This study uses a qualitative method of literature study (library research) in collecting its data. The literature study conducted is elaborating data and information obtained from books, journals, news, and other credible references related to the discussed topics or issues raised to strengthen the data and information being examined. The results of this study indicate that character education based on prophetic pedagogy is able to overcome student demoralization by considering prophetic pedagogical values such as humanization, liberation, and transcendence which are in line with Islamic religious education that makes the behavior of Prophet Muhammad SAW as a reference in daily life behavior.